ENERGY DIPLOMACY OF CHINA AND RUSSIA: MUTUALLY BENEFICIAL COOPERATION OR COMPETITION? (British Journal of Global Ecology and Sustainable Development, 2024)
This article provides an overview of collaboration in the energy sector between two influential states, namely China and Russia. The paper covers key aspects of energy diplomacy and its impact on global dynamics. Factors determining the nature of relations between Russia and China in the context of energy resources are analyzed. The article also assesses forecasts for the development of cooperation and potential challenges, offering a forward-looking perspective on the future energy interaction between these two countries.